Voltage-dependent regulation of Ca(V)2.2 channels by G(q)-coupled receptor is facilitated by membrane-localized β subunit - Keum, Dongil (The Rockefeller University Press, 2014)
G protein–coupled receptors (GPCRs) signal through molecular messengers, such as Gβγ, Ca(2+), and phosphatidylinositol 4,5-bisphosphate (PIP(2)), to modulate N-type voltage-gated Ca(2+) (Ca(V)2.2) channels, playing a crucial role in regulating synaptic transmission. However, the cellular pathways through which G(q)PCRs inhibit Ca(V)2.2 channel current are not completely understood. Here, we report that the location of Ca(V) β subunits is key to determining the voltage dependence of Ca(V)2.2 channel modulation by G(q)PCRs. Application of the muscarinic agonist oxotremorine-M to tsA-201 cells expressing M(1) receptors, together with Ca(V) N-type α1B, α2δ1, and membrane-localized β2a subunits, shifted the current-voltage relationship for Ca(V)2.2 activation 5 mV to the right and slowed current activation. Muscarinic suppression of Ca(V)2.2 activity was relieved by strong depolarizing prepulses. Moreover, when the C terminus of β-adrenergic receptor kinase (which binds Gβγ) was coexpressed with N-type channels, inhibition of Ca(V)2.2 current after M(1) receptor activation was markedly reduced and delayed, whereas the delay between PIP(2) hydrolysis and inhibition of Ca(V)2.2 current was decreased. When the Gβγ-insensitive Ca(V)2.2 α1C-1B chimera was expressed, voltage-dependent inhibition of calcium current was virtually abolished, suggesting that M(1) receptors act through Gβγ to inhibit Ca(V)2.2 channels bearing membrane-localized Ca(V) β2a subunits. Expression of cytosolic β subunits such as β2b and β3, as well as the palmitoylation-negative mutant β2a(C3,4S), reduced the voltage dependence of M(1) muscarinic inhibition of Ca(V)2.2 channels, whereas it increased inhibition mediated by PIP(2) depletion. Together, our results indicate that, with membrane-localized Ca(V) β subunits, Ca(V)2.2 channels are subject to Gβγ-mediated voltage-dependent inhibition, whereas cytosol-localized β subunits confer more effective PIP(2)-mediated voltage-independent regulation. Thus, the voltage dependence of G(q)PCR regulation of calcium channels can be determined by the location of isotype-specific Ca(V) β subunits.